Phosphorus-Substituted Azulenes Accessed via Direct Hafner Reaction of a Phosphino Cyclopentadienide - Gee, Anthony P.; Cosham, Samuel D.; Johnson, Andrew L.; Lewis, Simon E. (Synlett, 2017)
The Hafner azulene synthesis may be applied to the direct synthesis of phosphorus-substituted azulenes, when a phosphinocyclopentadienide is used as one of the reactants. The azulenyl phosphines produced in this fashion are preferentially isolated as the corresponding phosphine oxides or phosphine borane adducts.
Keywords: azulene; phosphine; pyrylium salt; cyclopentadienide; borane adduct